Media pembelajaran torah pedia untuk meningkatkan pengetahuan tokoh sejarah indonesia peserta didik sekolah dasar - Abdul Azis (Universitas Sebelas Maret, 2024)
Social Sciences are very useful in everyday life. Based on this, Social Sciences becomes important to learn. Even so, there are still many facts found in the field regarding social science learning outcomes very low. Learning media is one of the things that can affect the quality of learning mathematics. Based on the results of interviews and observations at several elementary schools in the Gajah Mada Kerten cluster, it is known thatthere is a problem of limitations of IPS learning media on national historical figures material. Therefore, this study aims to develop interactive learning media based on storylines articulated on national historical figures.This type of research is development research using the 4D research model (Define, design,develop, and disseminate). The implementation of this research was only carried out on development stage. Data collection techniques in this study used interviews, observation, documentation studies, and questionnaires. The results of this study are valid learning media based on the proportion of the material expert's assessment of 88.4% and the proportion of the media's assessment expert judgment of 93.2%. The results of this study are also in the form of learning practices media based on teacher assessment with a proportion of 96.4% and student assessment with the proportion was 91.54%.